A review of the spider wasp genus Austrosalius Turner, 1917 (Hymenoptera, Pompilidae), with the description of a new species - Loktionov, Valery M. (Zootaxa, 2021)
The Australasian spider wasp genus Austrosalius Turner, 1917 is reviewed for the first time. The genus comprises three species, of them Austrosalius mikhailovi Loktionov, sp. nov. is described and illustrated, based on female specimens from West Papua Province of Indonesia. The genus Austrosalius is newly reported from the island of New Guinea. The generic diagnosis and a key to the species are given.